Improving energy efficiency in massive MIMO system with non-ideal hardware / Abd Aziz Bakeri and Dr Nuridora Abdul Razak - Bakeri, Abd Aziz; Abdul Razak, Nuridora (2017)
Massive Multiple Input Multiple Output also known as Massive MIMO is promising nest generation for wireless network technology, with large number of antenna at base station mean targe scale radio frequency chains. It offer higher data rates with low energy consumption for better environment in green technology. This research focus on comparison energy efficiency between ideal hardware and non ideal hardware in Massive MIMO system. In this paper, energy effiency analyzes from N antenna at base station and single antenna user transceiver.Result shows massive Ml MO noo ideal hardware can achieve energy efficiency.